Diagnostic value of thromboelastogram and thrombus molecular markers in early detection of deep vein thrombosis in patients with lower extremity fracture - E. Jianfei; Mao Zheng; Wei Wei; Shaoping He; Chengliang Yuan; Zongyao Chen (European Journal of Medical Research)
Abstract Background Deep vein thrombosis (DVT) is an obstructive disease with a hindering venous reflux mechanism. The aim of this study was to identify independent risk factors for deep vein thrombosis (DVT) in patients with traumatic lower extremity fractures and assess the diagnostic value of thromboelastogram (TEG) and thrombus molecular markers. Methods Reviewed patients with lower extremity fractures were admitted from October 2022 to September 2023. DVT was screened using color Doppler ultrasonography postoperation. Patients were categorized into two groups: those with DVT (n = 61) and those without (n = 191). Logistic regression was utilized to analyze DVT risk factors in these patients, and the diagnostic effectiveness of each marker was determined using the receiver operating characteristic curve (ROC curve). Results Significant differences were found in the incidence of hip (44.8%), and tibia (16.4%) fractures in the DVT groups (P < 0.001). Elevated levels of tPAIC, PIC, sTM, TAT, APTT, and TEG parameters (angle, MA, and CI) were observed in the DVT group (P < 0.05). Multivariate logistic regression revealed that PIC, sTM, TAT, angle, MA, CI, Caprini score, and hip fracture were significant risk factors for DVT. Conclusions Patients with hip fractures showed a higher incidence of perioperative DVT. Factors such as PIC, sTM, TAT, angle, MA, CI, Caprini score, and hip fracture significantly contributed to the risk of DVT in traumatic lower limb fractures. Both thromboelastogram and thrombus molecular markers demonstrated strong diagnostic capabilities in the early detection of DVT, with comparable diagnostic efficiency.